Green Synthesis of Substituted Dihydropyrimidin-2(1H)-one by Using Zinc Chloride /Acetic Acid Catalytic System - Thorat, Bapu R.; Gurav, Ankita; Dalvi, Bharat; Sawant, Ashwini; Lokhande, Vikas; Mali, Suraj N. (Current Chinese Chemistry, 2021)
Background: Biginelli reaction is the most well-known and widely studied, multi-component reaction used for the direct synthesis of many biologically active 3,4-dihydropyrimidin-2(1H)-ones and their derivatives by reacting a β-keto ester/1,3-dicarbonyl compound, an aldehyde, and urea. It is catalyzed by different Bronsted and Lewis acids. Methods: The catalytic effect of different metal chlorides, such as sodium, potassium, magnesium, stannous, ferric, manganese, cupric, nickel, cobalt, and zinc, in absence and presence of acetic acid were studied. Results: The zinc, ferric, cupric, and cobalt chlorides were found to be more effective catalysts for Biginelli reaction at room temperature. The yield of the reaction increased with temperature for all catalytic systems. Acetophenone, cyclohexanone, acetyl acetone, and different β-ketoesters formed tetrahedropyrimidine in moderate to good yield, by using zinc chloride catalyst at room temperature in acetic acid. The efficiency of the catalyst was studied by treating different substituted aldehydes with 1,3-dicarbonyl compounds and urea at room temperature. Conclusion: The zinc chloride in acetic acid found to be an effective greener catalyst system for Biginelli reaction.
Keywords: Biginelli reaction